2013
DOI: 10.7314/apjcp.2013.14.4.2265
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulatory Network of MicroRNAs, Transcription Factors, Gene Alterations in Adrenocortical Cancer

Abstract: Several lines of evidence indicate that cancer is a multistep process. To survey the mechanisms involving gene alteration and miRNAs in adrenocortical cancer, we focused on transcriptional factors as a point of penetration to build a regulatory network. We derived three level networks: differentially expressed; related; and global. A topology network ws then set up for development of adrenocortical cancer. In this network, we found that some pathways with differentially expressed elements (genetic and miRNA) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…And Tong et al (2012) revealed that mutated gene AKT1, which also has a high potential of being influence on the mechanisms of NB, with other mutated genes play a key role on the key EGFR pathway in human Breast Cancer (BC). Furthermore, we found that this EGFR pathway might have a related network with MYC, which is as a related gene in NB and different-expressed gene in BC (Zhang et al, 2013). These indicated that the same different-expressed miRNAs or genes do have possibilities to influence on different human cancers, which also means it is possible that we can extract several miRNAs and genes having this feature and take some certain measurements to stop them differently expressing in order to helpfully prevent cancers if we sufficiently figure out the inter-relationship of different cancers and combine valid results together.…”
Section: Discussionmentioning
confidence: 83%
“…And Tong et al (2012) revealed that mutated gene AKT1, which also has a high potential of being influence on the mechanisms of NB, with other mutated genes play a key role on the key EGFR pathway in human Breast Cancer (BC). Furthermore, we found that this EGFR pathway might have a related network with MYC, which is as a related gene in NB and different-expressed gene in BC (Zhang et al, 2013). These indicated that the same different-expressed miRNAs or genes do have possibilities to influence on different human cancers, which also means it is possible that we can extract several miRNAs and genes having this feature and take some certain measurements to stop them differently expressing in order to helpfully prevent cancers if we sufficiently figure out the inter-relationship of different cancers and combine valid results together.…”
Section: Discussionmentioning
confidence: 83%
“…Both TFs can potentially bind to the CENPA promoter sequence indicating that they regulate CENPA transcription ( Grant et al, 2013 ). Previous studies have correlated CENPA with poor prognosis in ACC patients and identified E2F2 as an ACC-related TF ( Xia et al, 2019 ; Zhang et al, 2013 ). Although few studies have associated CREB3L3, MYBL2, HOXC11, ZIC2, ZNF282, DNMT1, TCF2, FLK4, and KLF6 with ACC progression ( DiFeo, Martignetti & Narla, 2009 ; Jain, Rechache & Kebebew, 2012 ), there is no evidence linking FOXM1 to ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Both TFs can potentially bind to the CENPA promoter sequence indicating that they regulate CENPA transcription 42 . Previous studies have correlated CENPA with poor prognosis in ACC patients and identi ed E2F2 as an ACC-related TF 43,44 . Although few studies have associated CREB3L3, MYBL2, HOXC11, ZIC2, ZNF282, DNMT1, TCF2, FLK4 and KLF6 with ACC progression 45,46 , there is no evidence linking FOXM1 to ACC.…”
Section: Discussionmentioning
confidence: 99%